Assemblies of 1D and 2D Copper(II) Chiral Coordination Polymers by Salicylaldehyde Schiff Bases: Synthesis, Crystal Structures, and Magnetic Properties1. Issue 1 (2nd August 2013) - Wang, Zhao‐Xi; Wu, Lin‐Fei; Hou, Xiao‐Kang; Shao, Min; Xiao, Hong‐Ping; Li, Ming‐Xing
Abstract Reaction of CuCl2·2H2O with chiral Schiff bases and sodium dicyanamide led to the formation of two chiral copper(II) coordination polymers, namely [Cu4(L1)2(dca)4]n (1) and [Cu2(L2)(μ‐Cl)(dca)(H2O)]n·nH2O (2) H2L1 = (1R, 3S)‐N′, N′′‐bis[salicylidene]‐1, 3‐diamino‐ 1, 2, 2‐trimethylcyclopentane, H2L2 = (1R, 3S)‐N′, N′′‐bis[3‐ethoxysalicylidene]‐1, 3‐diamino‐ 1, 2, 2‐trimethylcyclopentane, dca = dicyanamide. Both complexes were structurally characterized by elemental analyses, IR spectroscopy and single‐crystal X‐ray diffraction. Complex 1 exhibits a two‐dimensional polymeric structure formed by single dca bridging tetranuclear Cu4 units. Complex 2 displays a left‐handed helical chain structure constructed from Cu2 dimers with single dca bridges. The chirality of 1 and 2 was confirmed by circular dichroism (CD) measurements in solution. Both complexes exhibit strong antiferromagnetic couplings with J = –308(4) cm–1 for 1 and J = –123(1) cm–1 for 2 in 2–300 K.